DEAF PARENT AND A DEAF BROTHER: SOME PERSPECTIVES ON IDENTITY AS A HEARING CHILD GROWING UP IN A PREDOMINATELY DEAF FAMILY - Townshend, James (Sites: A Journal of Social Anthropology and Cultural Studies, 2008)
My mother father deaf, my brother deaf point-left, brother point-right, hearing, me what? me hearing but deaf heart.